Effects of hydrothermal treatment and low-temperature storage of whole wheat grains on in vitro starch hydrolysis and flour properties. (30th November 2022) - Abhilasha, Abhilasha; Kaur, Lovedeep; Monro, John; Hardacre, Allan; Singh, Jaspreet
Graphical abstract: Highlights: Hydrothermal treatment followed by cold-storage of whole wheat modified grain microstructure. Starch hydrolysis in different wheat formats was reduced because of starch retrogradation. Peak hot paste viscosity and final viscosity of flours from cold-stored grains were lower than their hydrothermally treated counterparts. Combination of hydrothermal treatment and retrogradation has potential to create low glycaemic wheat products. Abstract: This study evaluated the effect of hydrothermal treatment of whole wheat grains at 100 °C followed by cold-storage (4 °C/ 7 days) on the resulting grains, flakes, and flour characteristics. The extent of starch hydrolysis after oral-gastro-small intestinal digestion in vitro was significantly lower (p < 0.05) in intact grains, flakes, and flours from the cold-stored grains, 35.73 ± 0.34%, 49.92 ± 0.18% and, 89.04 ± 1.51%, than their non-cold-stored counterparts, 44.86 ± 0.24%, 58.73 ± 0.90% and, 95.96 ± 0.43%, respectively. Scanning electron micrographs, pasting properties, water retention capacities and relative crystallinity of the resulting flours revealed enhanced degree of gelatinisation with the treatment temperature; however, cold-storage of treated grains resulted in change in these properties due to the retrogradation of the starch. This study indicates that hydrothermal pre-treatment of grains followed by low-temperature storage for prolonged periods might help to reduce starch digestibility of wheat grains and their resulting products, and could be an effective strategy in developing reduced glycaemic impact grain products.